ЖАЛПАҚ ТИСЛИ КРЫСАНЫҢ АЗЫҚЛАНЫЎЫ ҲӘМ ИН ҚУРЫЛЫСЫ - Палўанова, Г.Ж.; Байгелдиева, Н.Ж. (FAN va JAMIYAT, 2023)
The damage caused by rodents, including the Flat-toothed rat, to the human economy in the form of feeding and nesting wounds, the information and instructions of those who develop measures for damage to it, and as a result, attention was paid to combating it.